Sex, Dr(a)gs and Rock’n’Roll: Diverse Masculinities of Glam Metal, Sleaze Metal and Hair Metal - Celina Jeray (Anglica. An International Journal of English Studies, 2021)
The following essay retraces the genre development and correlations of three 1980s hard rock subgenres: glam metal, sleaze metal and hair metal. This issue is considered, primarily, with reference to the theory of hegemonic and non-hegemonic masculinities developed by Raewyn Connell and reviewed against the theory of genre development by Jennifer C. Lena and Richard A. Peterson. Both theories are employed in order to underline the subtle differences between the subgenres, arguably linked to the masculinities performed by the artists’ assumed stage personas. Aside from the scholarly references, the research includes various interviews with the artists and music journalists, an analysis of over a hundred song lyrics and the vast repertoire of visual arts accompanying the music.